Os saberes da tradição da comunidade Segredinho na percepção das crianças - CONTENTE, Ariadne da Costa Peres (Universidade Federal do Pará, 2021)
This article aims to reflect on the traditional knowledge learned through artisanal fishing and the myth that involves the Segredo Lake from the children perception in the Segredinho community, CapanemaPA. This article is a part of the doctoral research in the Segredinho community, Capanema-PA in the northeastern Pará. Qualitative research was used and the data was obtained through a semi-structured interview. This interview was directed at two (02) children living in this community. The results showed that children develop knowledge linked to the composition, size, type of fish, fishing instruments, identification of species, the most suitable points for fishing and other through of socio-environmental practices knowledge daily. The artisanal fishing knowledge is acquired through the transmission and observation of the most experienced in the activity, which passes between generations. Fishing in Segredo Lake besides that an economic activity, unite mythic, symbolic and tradition aspects.